2013
DOI: 10.1093/eurheartj/ehs465
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tricuspid regurgitation on survival in patients with chronic heart failure: unexpected findings of a long-term observational study

Abstract: The prognostic impact of TR depends on the severity of CHF. While TR was significantly related with excess mortality in mild to moderate CHF, it provided no additive value in advanced disease when compared with established risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
102
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 27 publications
15
102
0
6
Order By: Relevance
“…These findings are consistent with those previously published (16,17) in patients with chronic heart failure where moderate/severe TR was associated with increased risk of mortality.…”
Section: J a C C : C A R D I O V A S C U L A R I N T E R V E N T I Osupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with those previously published (16,17) in patients with chronic heart failure where moderate/severe TR was associated with increased risk of mortality.…”
Section: J a C C : C A R D I O V A S C U L A R I N T E R V E N T I Osupporting
confidence: 93%
“…Several studies have reported an increased risk of mortality in chronic heart failure patients having moderate or severe TR (9,14,16,17).…”
mentioning
confidence: 99%
“…Moderate‐to‐severe TR is present in 30% to 50% of patients with severe mitral regurgitation and in 12% to 25% of patients with severe aortic stenosis 4, 24, 25, 26, 27, 28. TR has been shown to be an independent negative predictor of long‐term survival among the following: (1) patients with multivalvular disease undergoing surgical or transcatheter aortic and mitral valve treatment,1, 2, 4, 25 (2) patients with heart failure who are treated medically,24, 29 and (3) patients with severe isolated TR who are treated medically 30, 31. There is also a growing body of evidence suggesting a potential mortality benefit of early treatment of TR in both patients with isolated TR and those with TR concomitant with mitral valve disease 23, 30, 32.…”
Section: Discussionmentioning
confidence: 99%
“…Functional TR in the absence of leaflet abnormalities frequently occurs in patients with heart failure by annulus dilatation and leaflet tethering1, 2, 3 and is associated with unfavorable outcomes 8, 9, 10, 11. Koelling et al demonstrated that severe functional TR was an independent predictor for all‐cause mortality in 1421 patients with LVEF <35% 9.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of TR initiates a vicious cycle of further RV dilatation and dysfunction and, consequently, worsening of TR 7. TR severity is independently associated with worse survival in heart failure patients8, 9, 10, 11 as well as in patients with isolated TR 12, 13…”
Section: Introductionmentioning
confidence: 99%